Hyperbolic Isogonal Tilings from Uniform Edge Colorings - Abila, Agatha Kristel (Archīum Ateneo, 2024)
This paper presents the construction of an isogonal tiling from an edge coloring of a uniform tiling of the hyperbolic plane. In addition, it also discusses how the isogonal tiling can be transformed into a hyperbolic artwork by using motifs with appropriate symmetry properties as the edges of the tiling